Analytic Approximate for the Plasma Sheath Potential. (May 2016) - Martin, Pablo; Maass-Artigas, Fernando; Cortés-Vega, Luis
Abstract: Here a new analytic approximation for the Bhom Sheath Potential is presented, which is valid for any value of the characteristic parameter K, measuring the mean ion velocity. The procedure to obtain this approximation is different to those used by previous authors, because now, the characteristic exponential parameter λ, depends on the parameter K, as well as the wall potential ϕw . In previous works that parameter used to be function of K only, and all the approximation used to fail for K ≤ 1/2, which is not the case now.